Spiritualitas Pandemik: Tinjauan Fenomenologi Ibadah Di Rumah - Hasahatan Hutahaean; Bonnarty Steven Silalahi; Linda Zenita Simanjuntak (Evangelikal: Jurnal Teologi Injili dan Pembinaan Warga Jemaat, 2020)
This research departs from the facts in the reality that we faced since the determination of the COVID-19 pandemi in Indonesia. The churches convert every activity from the church into homes. This phenomenon brings researchers to the spirituality of the congregation during a pandemi with devotions at home. A qualitative approach with a methodological method is used to obtain teaching from these experiences on the spiritual side. With a sample of one hundred respondents from four Churches Congregation who held every devotion activities at home, they realized that the opportunity to understand God's sovereignty upon the whole world, and increasingly surrendered to Him (arround 94%). The respondent composition is dominated by attending live streaming (96%) while doing devotion at home with church printed-out services is 3%. Several respondents found 2.6% sharing the Word by themself in the devotion session at home. By this research, there is hope for churches to take a serious look to the digital field by forming a digital commission/department or another designation with the task of serving the online services because advances in information technology become tools that cannot be ignored for the advancement of church services and developments. The pandemi did not pose a threat to the congregation to grow and rush on the spiritual side. Penelitian ini berangkat dari fakta di lapangan yang ada sejak penentuan pandemik korona jenis baru di Indonesia. Gereja-gereja mengalihkan ibadah di gereja menjadi di rumah-rumah. Fenomena ini membawa peneliti kepada sisi spiritualitas jemaat selama pandemik dengan ibadah di rumah. Pende-katan kualitatif dengan metode metodologi dipakai untuk mendapatkan pengajaran dari pengalaman ter-sebut bagi sisi spiritualitas. Dengan sample seratus responden dari empat jemaat yang mengadakan iba-dah di rumah, di temukan hasil diantaranya menyadari kesempatan untuk melihat kuasa Tuhan atas seisi dunia, dansemakin berserah pada-Nya (sekitar 94%). Komposisi responden didominasi mengikuti ibadah dengan live streaming (92%) sedangkan ibadah di rumah dengan tata ibadah dari gereja sebanyak 5%. Dari sejumlah responden didapati 2,6% berbagi Firman Tuhan (sharing) pada sesi khotbah dalam kebak-tian di rumah. Dengan penelitian ini ada harapan kepada gereja-gereja untuk menatap dengan serius bidang digital dengan (misalnya) membentuk komisi/sie khusus digital atau sebutan lain dengan tugas pa-da pelayanan dunia daring karena kemajuan teknologi informasi menjadi tools yang tidak dapat diabaikan demi kemajuan pelayanan dan perkembagan gereja. Masa pandemik tidak menjadi ancaman kepada warga jemaat untuk bertumbuh dan bergegas dalam sisi spiritualitas.